Inequalities, agency, and well-being: Conceptual linkages and measurement challenges in development - Douglas A. Hicks (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
The capabilities approach has emphasized that inequalities can be analyzed in various dimensions of human functioning. Indicators of these inequalities can be incorporated into assessments of well-being. The capabilities approach also highlights the intrinsic importance of agency and demonstrates empirically that agency is instrumentally valuable for achieving various functionings. This paper draws together these discussions to delineate the relationships among inequalities, agency, and well-being of disadvantaged persons. A person's relative deprivation (e.g., being illiterate or being in ill-health) negatively affects her well-being and contributes to her lack of agency. Conversely, some (but not all) expressions of agency by disadvantaged persons can help reduce inequalities. This model provides a complex understanding of the dynamics of deprivation—and its alleviation. The paper closes by considering ways agency and inequalities could be incorporated alongside well-being into indicators of development. – development ; inequality ; gender ; well-being ; agency ; capability ; distribution ; Sen
Keywords: I32; J16; D63; 330; Armut; Lebensqualität; Geschlecht; Einkommensverteilung